The development of the term [enypostatos] from Origen to John of Damascus - Gleede, Benjamin (Supplements to Vigiliae Christianae, 2012)
Examining the usage of the term enypostatos throughout the Patristic period, this study illustrates the gradual change in its meaning from stressing the hypostatical independence of the trinitarian persons to upholding the reality of Christ's two natures in his unique hypostasis.